G457(P) Admission processes in HPA-an general hospital, myanmar. (25th October 2020) - Ivey, E; Win, HH; Chan, HMM; Oo, TT; Wootton, M; Maconochie, I
Abstract : Background: Myanmar faces challenges of rising patient numbers, with state and district hospitals particularly feeling the strain. In Kayin state 78% of the population live in rural areas. Affected by recent conflict and economic migration of the working-age population, children under 15 make up 36% of the population. The hospital presented here is a 200-bedded state hospital, serving a population close to 800, 000. There is little data describing patterns in acute paediatric admissions to state hospitals in Myanmar. Aim: To describe the processes of paediatric admission to state hospital and the characteristics of admitted children by age, referral source and rates of admissions. Methods: Logbook records from the emergency department (OPD) and Child Ward (CW) were reviewed for the period March 2018–February 2019. OPD attendances were analysed by age and outcome. Records were reviewed to establish the proportion of admitted patients referred from other hospitals. Results: Potential outcomes from OPD assessment were discharge, daily OPD review, clinic referral or admission. Children <12 y with medical problems are admitted to CW; children >12 y and those <12 y with surgical problems are admitted to adult wards, under adult teams. Children accounted for 27% of OPD attendances. On average, 1475 children attended OPD each month. 40.3% of children attending OPD were admitted to CW on average, rising significantly to 48.8%(p≤0.001) in the rainy season (June to September). Admissions were highest in children <2 years. Referrals from other hospitals represented 4.7% of admissions and this figure rose throughout the year. Conclusions: High admissions rates from OPD reflect the challenges of serving a geographically large and rural population. In the rainy season, dengue fever flourishes and fear of missing this diagnosis in febrile children may influence clinician behaviour during this period. Admission rates were highest in July with a second peak in September. OPD attendances peaked later (October). We suggest that road flooding in August and September restricts travel, limiting total attendances. With the state hospital's increasing role as a receiving centre from smaller hospitals, further study is needed to characterise the burden of disease in children presenting to hospital and guide service development in Myanmar.